Factors associated with achieving intraocular pressure lower than 15 mmHg by Trabectome surgery in primary open-angle glaucoma - Kentaro Nakamura (Nature Portfolio, 2021)
Abstract To assess good prognostic factors of Trabectome surgery in primary open-angle glaucoma (POAG), clinical records of patients with POAG who underwent Trabectome surgery with/without cataract surgery as the first additive therapy to eye drops between January 2015 and March 2018 were retrospectively reviewed. Overall, data of 79 eyes (79 patients; 50 men; mean age, 68.0 years) up to postoperative 24 months were analyzed. Their mean intraocular pressure (IOP) was 20.4 ± 6.0 mmHg at baseline. Forty-two eyes (53.2%) achieved an IOP < 15 mmHg and ≥ 20% reduction from baseline without additional treatments. Phakic eyes had a better survival probability than pseudophakic eyes after adjusting for age, sex, baseline IOP, best-corrected visual acuity, and eye drop score (hazard ratio 3.096; 95% confidence interval [95% CI] 1.367–7.013; P = 0.007). Phakic eyes treated with combined Trabectome and cataract surgeries (mean survival time, 22.250 months; 95% CI 17.606–26.894) had a better survival probability than pseudophakic eyes treated with Trabectome surgery only (mean survival time, 12.111 months; 95% CI 8.716–15.506; P = 0.009) after the adjustment. Among the eyes treated with Trabectome surgery only, phakic eyes required significantly less additional treatments than pseudophakic eyes (P = 0.04). Trabectome surgery may be indicated for phakic eyes with POAG in addition to eye-drop therapy.